Online Games and Student Achievement: A Case Study at Al-Islamiyah Elementary School: Game Online dan Prestasi Siswa: Studi Kasus SD Al-Islamiyah - Sa’diah, Sayyidati; Efendi, Nur (Universitas Muhammadiyah Sidoarjo, 2025)
General Background : The rise of digital technology has introduced modern challenges to education, particularly concerning students' engagement with online games. Specific Background : This study specifically examines the effects of online game addiction on fourth-grade students at Al-Islamiyah Putat, Tanggulangin Elementary School. Knowledge Gap : While the general impacts of online gaming are known, there is a gap in understanding the specific effects and effective mitigation strategies within this particular school context. Aims : The research aims to analyze the positive and negative consequences of online game addiction on students' academic motivation and behavior. Results : Findings indicate both positive and negative outcomes. Positively, students easily learn foreign languages and develop technological literacy. Negatively, students show poor emotional control, lack of motivation for both academic and non-academic achievements, and have reduced concentration in class. Teachers address this with a reward and punishment system. Novelty : The study's novelty lies in its focused analysis of a specific elementary school, providing a detailed case study on the dual impacts of online gaming. Implications : The research suggests that the primary factor in addiction is the home environment, emphasizing the need for parental supervision and for teachers to employ effective strategies to manage this issue. Highlights : Online gaming has both positive and negative effects on elementary students' learning and behavior. Positive effects include learning foreign languages and developing technological skills, while negative effects involve emotional issues and poor concentration. The main factor in online game addiction among students is their home environment, underscoring the importance of parental supervision. Keywords : Online Gaming Addiction, Elementary Education, Teacher Strategies, Learning Motivation, Social Skills